COMPREHENSIVE ANALYSIS ON OPTIMIZING LABORATORY AND BLOOD BANK SERVICES TO SUPPORT EMERGENCY HEALTHCARE NEEDS - 1Theyab Ali Mohammed Almuhri, 2Ishag Ali Al Ishag, 3Abdulaziz Farisalduways, 4Faisal Zedan Ali Al Dhoushan, 5Muhammad Saleh Mahdi Al Harth, 6Jamilah Mubarak Saadalfaraj, 7Mohammed Abdullah Hussain Alsoma, 8Salehah Saeedalyami (Chelonian Research Foundation, 2023)
The provision of efficient laboratory and blood bank services is essential to meeting pressing therapeutic needs. This article comprehensively surveys the progress made by these administrations to extend emergency response capacity. This paper explores procedures to move forward the effectiveness, adequacy, and proficiency of the unit, test, and blood bank by analyzing important information, operational methods, and results. Discoveries indicate that utilizing progressed innovation, making strides in asset assignment, fortifying communication, and empowering collaboration are critical to accomplishing these objectives. The discourse highlights the significance of these discoveries and offers proposals for policymakers and professionals to progress emergency medical room capacity. Keywords: Laboratory services, Blood bank services, Emergency healthcare, Optimization, Technology, Resource allocation, Collaboration.